AN ANALYSIS OF SLANG WORDS ABBREVIATION IN AMERICAN CAPTION ON INSTAGRAM: A SOCIOLINGUISTICS APPROACH - Napitu, Fera Ekawaty; Suhardianto, Suahrdianto (SCIENTIA JOURNAL, 2020)
This research is a study of language phenomena that occurs in social media. Instagram users often take action to upload pictures, videos, and memes by adding text and in English called 'Caption'. The caption implies a youth style that is abbreviated and practical. The language style is researched and there is the use of slang. The purpose of this study was to find out the construction and meaning of slang.The reason for using slang language found in the caption used by American on Instagram. Regarding this phenomenon, the researcher is interested discussing the phenomenon of abbreviated slang words found in the caption on Instagram social media. Furthermore, this study is a study qualitative descriptive method. The data is taken from Instagram accounts in a certain period of time. Data was collected by researchers for two months from middle of March to middle of May. The data collected is qualitative data. The data collection method used in this research is the Record method. The data analysis method used in this research is the method of matching and Agih. The data presentation method used in this research is an informal method. Referring to the three methods, the researcher used the Sudaryanto theory.